Analisis Pengaruh Persepsi Kebermanfaatan, Persepsi Kemudahan dan Persepsi Risiko Terhadap Minat UMKM untuk Bertransaksi Menggunakan Fintech/Financial Technology Sebagai Layanan Pembayaran Digital: Studi pada UMKM Kabupaten Nganjuk - Acha Bella Firdayanti; Erna Puspita; Andy Kurniawan (Masyarakat Ekonomi Syariah Bogor, 2024)
This research is motivated by technological developments which are accelerating rapidly and penetrating various sectors of life. Technological progress has had many positive impacts, one of which is on the economic sector. Starting from limitations in making payments, an innovation was created that made things easier and faster. The aim of this research is to analyze whether perceived usefulness, perceived convenience and perceived risk partially and simultaneously UMKM influence interest in making transactions using Fintech/Financial Technology as a digital payment service. This research uses a quantitative approach with the causality method. In this research, the population of UMKM taken was operating in the culinary sector who were registered with the Nganjuk Regency Cooperatives and Micro Enterprises Service, totaling 544 UMKM. The sampling technique used a purposive sampling technique using the Slovin formula and the number of samples used in the research was 85 respondents obtained by distributing questionnaires/google forms. The tests carried out in this research used SPSS version 25 with multiple linear regression analysis methods. The conclusion of this research shows that perceived usefulness, perceived convenience and perceived risk partially and simultaneously have a significant influence on UMKM interest in using fintech as a digital payment service.